Genetics of Bladder Malignant Tumors in Childhood - Zangari, Andrea; Zaini, Johan; Gulia, Caterina (Current Genomics, 2016)
Bladder masses are represented by either benign or malignant entities. Malignant bladder tumors are frequent causes of disease and death in western countries. However, in children they are less common. Additionally, different features are found in childhood, in which non epithelial tumors are more common than epithelial ones. Rhabdomyosarcoma is the most common pediatric bladder tumor, but many other types of lesions may be found, such as malignant rhabdoid tumor (MRT), inflammatory myofibroblastic tumor and neuroblastoma. Other rarer tumors described in literature include urothelial carcinoma and other epithelial neoplasms. Rhabdomyosarcoma is associated to a variety of genetic syndromes and many genes are involved in tumor development. PAX3-FKHR and PAX7-FKHR (P-F) fusion state has important implications in the pathogenesis and biology of RMS, and different genes alterations are involved in the pathogenesis of P-F negative and embryonal RMS, which are the subsets of tumors most frequently affecting the bladder. These genes include p53, MEF2, MYOG, Ptch1, Gli1, Gli3, Myf5, MyoD1, NF1, NRAS, KRAS, HRAS, FGFR4, PIK3CA, CTNNB1, FBXW7, IGF1R, PDGFRA, ERBB2/4, MET, BCOR. Malignant rhabdoid tumor (MRT) usually shows SMARCB1/INI1 alterations. Anaplastic lymphoma kinase (ALK) gene translocations are the most frequently associated alterations in inflammatory myofibroblastic tumor (IMT). Few genes alterations in urothelial neoplasms have been reported in the paediatric population, which are mainly related to deletion of p16/lnk4, overexpression of CK20 and overexpression of p53. Here, we reviewed available literature to identify genes associated to bladder malignancies in children and discussed their possible relationships with these tumors.
Keywords: Malignancy